The promotion of stress tolerant Symbiodiniaceae dominance in juveniles of two coral species under simulated future conditions of ocean warming and acidification - Terrell, Alyx P.; Marangon, Emma; Webster, Nicole S.; Cooke, Ira; Quigley, Kate M. (Frontiers in Ecology and Evolution, 2023)
The symbiotic relationship between coral and its endosymbiotic algae, Symbiodiniaceae, greatly influences the hosts’ potential to withstand environmental stress. To date, the effects of climate change on this relationship has primarily focused on adult corals. Uncovering the effects of environmental stress on the establishment and development of this symbiosis in early life stages is critical for predicting how corals may respond to climate change. To determine the impacts of future climate projections on the establishment of symbionts in juvenile corals, ITS2 amplicon sequencing of single coral juveniles was applied to Goniastrea retiformis and Acropora millepora before and after exposure to three climate conditions of varying temperature and pCO2 levels (current and RCP8.5 in 2050 and 2100). Compared to ambient conditions, juvenile corals experienced shuffling in the relative abundance of Cladocopium (C1m, reduction) to Durusdinium (D1 and D1a, increase) over time. We calculated a novel risk metric incorporating functional redundancy and likelihood of impact on host physiology to identify the loss of D1a as a ‘low risk’ to the coral compared to the loss of “higher risk” taxa like D1 and C1m. Although the increase in stress tolerant Durusdinium under future warming was encouraging for A. millepora, by 2100, G. retiformis communities displayed signs of symbiosis de-regulation, suggesting this acclimatory mechanism may have species-specific thresholds. Whilst this study cannot specifically disentangle the individual effects of temperature and pCO2, it does provide valuable insights into the impacts of both stressors combined. These results emphasize the need for understanding of long-term effects of climate change induced stress on coral juveniles, and their potential for increased acclimation to heat tolerance through changes in symbiosis.